KISAH DAUD A.S DALAM PERSPEKTIF AL-QUR’AN - Muhammad, Muhammad Thaib (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2018)
The story of David a.s. in the history of the religious world is a very important one, because all the religions of the world recognize that David a.s is descended from Ya'qub a.s descendant of his son Yahuza. Allah Almighty has made him a prophet and a king. The Bible scholars have mentioned it in the Bible and in the Bible. God has revealed the book of Psalms as a guide in carrying out his preaching. Allah believes in the Qur'an: "" وآﺗﻴﻨﺎ داود زﺑﻮرا (we have descended to David the book of Psalms). ) for 356 years During that time the Children of Israel became a weak and weak people, even though they lived in wickedness and wickedness and abandoned the law of Allah Sw. As a goat had no shepherd, God sent down a prophet called Shamwil. with great enthusiasm they were able to defeat their enemies A young boy named David immediately took up his challenge. But Jalut thought the challenge was incomparable. Then David and the men of Israel were able to kill him and his men. Once David's name became known among the Children of Israel, they finally adopted him as king. When David was 40 years old God raised him up as a prophet and referred to Psalm as his holy book. David.s has a beautiful and beautiful voice. While reading the book of Zabur in a melodious voice, so that the bird in flight immediately stopped to remember Allah Swt. The Messenger of Allah (may peace be upon him) praised the beauty of David's voice. After carrying out his pamphlet among the Children of Israel, he died at the age of 70. In the history of the Islamic scholar David at the age of 100, and was buried in the Temple of Palestine.